2*x-y+y*z=-4 2*x+y+z=3 -x-3*y+2*z=-9

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:
53 уравнение:

Решение

Вы ввели
[TeX]
[pretty]
[text]
2*x - y + y*z = -4
$$y z + 2 x - y = -4$$
2*x + y + z = 3
$$z + 2 x + y = 3$$
-x - 3*y + 2*z = -9
$$2 z + - x - 3 y = -9$$
Быстрый ответ
[TeX]
$$x_{1} = - i$$
=
$$- i$$
=
-1*i

$$z_{1} = i$$
=
$$i$$
=
1*i

$$y_{1} = 3 + i$$
=
$$3 + i$$
=
3 + 1*i
$$x_{2} = i$$
=
$$i$$
=
1*i

$$z_{2} = - i$$
=
$$- i$$
=
-1*i

$$y_{2} = 3 - i$$
=
$$3 - i$$
=
3 - 1*i